PENYUSUNAN LAPORAN KEUANGAN FISKAL PADA KOPERASI SERBA USAHA KARYAWAN PEMERINTAH KOTA SEMARANG TAHUN 2014 - Meta Rizky Annisa; Adilistiono - Adilistiono (Politeknik Negeri Semarang, 2016)
This final project aims to prepare financialstatements fiscal and determine the factorscausing the difference between thecommercial financial statements with thefinancial statements of fiscal EmployeesMultipurpose Cooperative EnterprisesSemarang government Year 2014. The dataused in the preparation of this final projectthat the financial statements, a list of fixedassets, a general overview and organizationalstructure Employees MultipurposeCooperative Enterprises Semarang CityGovernment. The data was obtained using thetechnique of data collection methods, namelyby interviewing the Business MultipurposeCooperative Semarang City GovernmentEmployees and through the literature thatrelated to the final project. While writingmethod used is the method description andmethod of exposition. Based on the results offiscal reconciliation there is a differencebetween commercial income with taxableincome of Rp 331,405,469.95. The differenceis due to differences in the recognition ofincome and expenses between commercialaccounting tax accounting ie permanentdifferences and timing differences. In fiscalreconciliation are also positive fiscalcorrection and negative fiscal correctionwhich then generates taxable income used asa basis for the calculation of tax payable.